Towards a threat assessment framework for consumer health wearables - Mnjama, Javan Joshua (Rhodes University, Faculty of Commerce, Department of Information Systems, 2018)
The collection of health data such as physical activity, consumption and physiological data through the use of consumer health wearables via fitness trackers are very beneficial for the promotion of physical wellness. However, consumer health wearables and their associated applications are known to have privacy and security concerns that can potentially make the collected personal health data vulnerable to hackers. These concerns are attributed to security theoretical frameworks not sufficiently addressing the entirety of privacy and security concerns relating to the diverse technological ecosystem of consumer health wearables. The objective of this research was therefore to develop a threat assessment framework that can be used to guide the detection of vulnerabilities which affect consumer health wearables and their associated applications. To meet this objective, the Design Science Research methodology was used to develop the desired artefact (Consumer Health Wearable Threat Assessment Framework). The framework is comprised of fourteen vulnerabilities classified according to Authentication, Authorization, Availability, Confidentiality, Non-Repudiation and Integrity. Through developing the artefact, the threat assessment framework was demonstrated on two fitness trackers and their associated applications. It was discovered, that the framework was able to identify how these vulnerabilities affected, these two test cases based on the classification categories of the framework. The framework was also evaluated by four security experts who assessed the quality, utility and efficacy of the framework. Experts, supported the use of the framework as a relevant and comprehensive framework to guide the detection of vulnerabilities towards consumer health wearables and their associated applications. The implication of this research study is that the framework can be used by developers to better identify the vulnerabilities of consumer health wearables and their associated applications. This will assist in creating a more securer environment for the storage and use of health data by consumer health wearables.
Keywords: Activity trackers (Wearable technology); Computer networks -- Security measures; Data protection; Information storage and retrieval systems -- Security systems; Computer security -- Software; Consumer Health Wearable Threat Assessment Framework; Design Science Research